Tinjauan Hukum Konsep Hak Menguasai Negara Dalam Penetapan Kawasan Hutan - Ahmad Maulana Anha; Eman Solaiman (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
Article 570 of the Civil Code, which is still in use today, also states that